1997
DOI: 10.1016/s1074-7613(00)80523-3
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Positive Selection of CD4 T Cells in Mice Displaying Altered Repertoires of MHC Class II–Bound Self-Peptides

Abstract: The role of self-peptides in positive selection of CD4+ T cells has been controversial. We show that some self-peptides are presented by the MHC class II molecule I-A(b) in mice lacking Ii or H-2M but not in mice expressing a transgene-encoded peptide fused to I-A(b). In experiments using specific antibodies to block selection, these low-abundance self-peptides were implicated in the positive selection of some CD4+ T cells in H-2M-/- mice. However, all three mutant backgrounds failed to positively select two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
182
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(190 citation statements)
references
References 48 publications
8
182
0
Order By: Relevance
“…TEa CD4 ϩ T cells express Thy1.1 (CD90.1) and V␤6 and recognize the I-E d ␣-chain peptide 52-68 (pE␣) 3 presented by I-A b (19). Thy1.1-C57BL/6NCr (B6) (H-2 b ) mice were purchased from Charles River Laboratories through a contract with the National Cancer Institute of the National Institutes of Health, and were used as syngeneic recipient mice for adoptive transfer studies.…”
Section: Mice and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEa CD4 ϩ T cells express Thy1.1 (CD90.1) and V␤6 and recognize the I-E d ␣-chain peptide 52-68 (pE␣) 3 presented by I-A b (19). Thy1.1-C57BL/6NCr (B6) (H-2 b ) mice were purchased from Charles River Laboratories through a contract with the National Cancer Institute of the National Institutes of Health, and were used as syngeneic recipient mice for adoptive transfer studies.…”
Section: Mice and Reagentsmentioning
confidence: 99%
“…To develop a model system that would give us control over the kinetics of TCR occupancy in vivo, we made use of the Y-Ae mAb that specifically recognizes pE␣/I-A b complexes and competes for binding with the TCR on the TEa T cells (19,21). One million CFSE-labeled CD4 ϩ TEa T cells were again adoptively transferred into B6 mice and challenged with EaRFP/LPS for a period of 120 h. Y-Ae mAb was also administered to the mice at various time points following the Ag injection.…”
Section: Optimal Ag-induced Cell Cycle Progression Requires Uninterrumentioning
confidence: 99%
“…This argues that peptide diversity, although present in the normal situation, is not important in T cell development. However, it has recently been shown that at least two of these approaches did not truly limit the peptide presentation to a single face (19,20). Additionally, the small percentage of MHC molecules presenting diverse self peptides was shown to be important in selecting T cells.…”
Section: Positive Selection Is Limited By Available Peptide-dependentmentioning
confidence: 99%
“…These clonal hybrids (nearly 500) were then tested for reactivity with APC from wild-type B6, H2-DM-deficient, Ii-deficient, A b EpIi Ϫ , and MHC class II-deficient mice (all from the H2 b haplotype). MHC class II molecules in these mice display varying degrees of class II cell-surface expression levels and peptide diversity: in B6 mice A b class II molecules are bound by a wide gemish of self-peptides; in H2-DM-deficient mice, A b molecules are expressed at normal levels and are mostly bound by a peptide, CLIP, derived from the MHC class II-associated Ii chain (41, 43, 44), but some contamination by non-CLIP peptides has been noted (45,46); in Ii-deficient mice, A b surface expression is reduced ϳ10-fold, and these molecules are thought to be occupied by low-affinity peptides (40,(47)(48)(49); in A b EpIi Ϫ mice, A b surface expression is reduced ϳ10-fold, and these complexes are bound by Ep (7); finally, MHC class II-deficient mice lack class II surface expression altogether (42,50). The reactivity of these hybrids was graded strong, weak, or none, when IL-2 produced by the hybrids was Ͼ50, 10 -50, or Ͻ10%, respectively, of the IL-2 produced when the hybrids were stimulated with wild-type B6 cells (Table I).…”
Section: Few H2-a B -Specific Alloreactive Cd4 ϩ T Cells Recognize Apmentioning
confidence: 99%
“…not all class II molecules in these mice are bound by CLIP (45,46). The experimental system used here does not have this limitation, because it is well-established that A b EpIi Ϫ mice express only a single peptide species (Ep) on their class II molecules (7,45).…”
Section: Peptide-dependence Of Alloreactive T Cell Responsesmentioning
confidence: 99%